Algoritma C4.5 dalam Penentuan Jurusan Siswa Baru - Siti Monalisa Monalisa; Fakhri Hadi (Ultimatics : Jurnal Teknik Informatika, 2020)
Based on ministerial regulations for curriculum 13 regarding specialization majors at the high school level from of entering class X. Then MAN 1 Inhil applied departmental arrangements that begin by including several indicators that are consistent with the results of testing, interviews, and student interest. Assessing in this departmental setting is very simple by summing each indicator's values and gathering the whole to produce an average value. If the value is fulfilled then the student is grouped based on their interests. This can lead to errors in the school's decision-making because this can lead to responses to student interests. Therefore we need methods and algorithms to help make decisions well. One algorithm that can be used is C4.5 algorithm which is an extension of ID3. The C4.5 algorithm used to classify majors with three indicators namely Natural Sciences, Social Sciences and Religion. The results showed that based on 360 data form the recapitulation result of student registrans, 71 data were obtained that had religious majors, 71 religious data were classified completely by C4.5. Furthermore, of the 144 data that have natural science majors, 123 data are fully classified, 20 data are approved as IPS, and 1 data is classified as religion. Of the 146 data that have majors in social studies, 120 are correct rules, 25 data are classified as natural sciences. Thus it can be concluded that the C4.5 algorithm has a success rate of 87.22% so that it can be used in decision making where most of the data is numeric.